Ethnicity and long-term course and outcome of psychotic disorders in a UK sample: the AESOP-10 study - Morgan, Craig; Fearon, Paul; Lappin, Julia M.; Heslin, Margaret; Donoghue, Kim; Lomas, Ben; Reininghaus, Ulrich A.; Onyejiaka, A.; Croudace, T.; Jones, Peter B.; Murray, Robin M.; Doody, Gillian A.; et al. (Royal College of Psychiatrists, 2018)
Background